Bezpieczeństwo teleinformatyczne w świetle Europejskiej Konwencji o cyberprzestępczości - Skrzypczak, Jędrzej (Przegląd Strategiczny, 2011)
The subject of this paper is the analysis of the main regulation of the the European Convention on Cybercrime. In particular, it attempts to answer the question whether the Convention provides sufficient level of European IT security.